Modelagem de apreçamento de índices setoriais no Brasil - Silveira, Lucas Camillo Ribeiro da (2019)
The purpose of this study was to model the asset prices of the Brazilian Stock Exchange sector indexes. The starting points were the CAPM and the model proposed by Treynor and Mazuy, to which a new regressor variable was added, creating our own model. We also aimed to test the stability of the parameters of the new model over time, applying statistical techniques to identify and date structural breaks in its parameters. The three models were estimated for the full period of data available for each index and the results indicate that the new model has greater explanatory power than the others and better describes the relationship between an asset’s and the market’s excess returns. The structural break tests identified the occurrence of changes in the parameters of the new model for all indexes. The data samples for each index were divided in sub periods for each break identified. The results of the estimation of our own model for each index sub period indicate that its parameters vary greatly over time, in both their statistical significance and their values, as does its explanatory power.